2016
DOI: 10.1007/s00220-016-2759-8
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of the Phase Transition for Planar Random-Cluster and Potts Models with $${1 \le q \le 4}$$ 1 ≤ q ≤ 4

Abstract: We prove that the q-state Potts model and the random-cluster model with cluster weight q > 4 undergo a discontinuous phase transition on the square lattice. More precisely, we show 1. Existence of multiple infinite-volume measures for the critical Potts and random-cluster models, 2. Ordering for the measures with monochromatic (resp. wired) boundary conditions for the critical Potts model (resp. random-cluster model), and 3. Exponential decay of correlations for the measure with free boundary conditions for bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
219
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 124 publications
(224 citation statements)
references
References 83 publications
3
219
1
1
Order By: Relevance
“…Our results for q c , in particular that of the honeycomb lattice, stand in contrast to the well known result q c = 4 of the usual model [4,5,7,8].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results for q c , in particular that of the honeycomb lattice, stand in contrast to the well known result q c = 4 of the usual model [4,5,7,8].…”
Section: Discussioncontrasting
confidence: 99%
“…His findings were believed to be lattice independent [6]. Recently, Duminil-Copin et al [7,8] have rigorously confirmed Baxter's predictions using the random cluster representation [9] of the nearest-neighbor interaction model.…”
Section: Introductionmentioning
confidence: 86%
“…The proof relies on a result of Russo, Seymour, and Welsh [23,24] that relates crossing probabilities for rectangles with different aspect ratios. Recently the boxcrossing property has been extended to planar percolation processes with spatial dependencies, e.g., continuum percolation [1,26] or the random-cluster model [10].…”
Section: Russo-seymour-welsh Theory and Power Law Decay On Slabsmentioning
confidence: 99%
“…On Z 2 , the continuity of the phase transition was recently proven [DCST14] for dependent percolation models known as random-cluster models with cluster-weight q ∈ [1, 4] (the special case q = 1 corresponds to Bernoulli percolation). The continuity of the phase transition for q = 1 and 2 was previously established by Harris [Har60] and Onsager [Ons44] respectively.…”
Section: Two Generalizationsmentioning
confidence: 99%